ANALISIS GAYA HIDUP, PERSEPSI DAN KELOMPOK ACUAN TERHADAP KEPUTUSAN PEMBELIAN - Rokhmad Budiyono; Dina Safira; Eni Puji Estuti (JURNAL STIE SEMARANG, 2022)
The purpose of this study was to determine the effect of lifestyle, perception and reference group on the decision to purchase silver jewelry at Sinar Silver Kudus Store. This type of research is descriptive quantitative research instrument in the form of a questionnaire using a Likert scale. The population in this study were all silver jewelry consumers at the Sinar Silver Kudus Store. The sampling technique in this study was accidental sampling with a sample of 97 respondents. The method of analysis in this study is Multiple Linear Regression Analysis which is used to test the hypothesis, using SPSS software version 23.00. This study uses 4 variables, namely 3 independent variables and 1 dependent variable, the independent variables consist of lifestyle, perception, reference group. While the dependent variable is the purchase decision. The results showed that partially the lifestyle variable had a positive and significant effect on purchasing decisions, partially the perception variable had a positive and significant effect on purchasing decisions, partially the reference group variables had a positive and significant effect on purchasing decisions. The results showed that purchasing decisions can be improved by paying attention to lifestyle, perceptions and reference groups.